ANALISIS KEBERLANJUTAN PENGEMBANGAN KAWASAN WISATA PANTAI PASIR PUTIH TONRANGENG (PAPUTO) KECAMATAN BACUKIKI BARAT KOTA PAREPARE - Zulvinar Syahrani; Asmidar Asmidar; Asbar Asbar; Syahrul Djafar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
Pantai Pasir Putih Tonrangeng (Paputo) is a tourist destination in Parepare City that has great potential to be developed. However, the development of this tourist area needs to be carried out sustainably so that its benefits can be felt in the long term by the community without damaging the environment.This study aims to: (1) analyze the sustainability status of the development of the Paputo tourism area based on five dimensions (ecological, economic, social, infrastructure, and institutional); (2) identify the factors contributing to the sustainability of the Paputo tourism area; The research uses the Multi-Dimensional Scaling (MDS) method using the Rapshore application. The results show that the ecological and social dimensions fall into the fairly sustainable category, the economic dimension is categorized as less sustainable, while the infrastructure and institutional dimensions are considered sustainable. The study also identifies key sensitive attributes as leverage factors in the sustainability of Paputo’s tourism development. Sensitive attributes in the ecological dimension include freshwater availability, coastal land cover, beach slope, beach width, and seabed material. In the economic dimension, they include the development of other tourism services, tourist retribution, and increased household income. For the social dimension, the sensitive attributes are tourism education and training, the application of science and technology, and environmental cleanliness. In the infrastructure dimension, the leverage attributes are clean water, facilities and infrastructure, and transportation access. Lastly, in the institutional dimension, the key sensitive attributes are local government regulations (Perda), local norms/laws/customs, and the role of local community institutions